PERCEPTION OF TAXPAYERS’ TOWARDS E-FILE ADOPTION - Mohammad, Anees; Kumar, Mukesh (International Journal of Research -GRANTHAALAYAH, 2017)
This paper try to build up an perceptive of the factors that influence citizens’ adoption of electronic tax-filing services and to discuss taxpayer perception and satisfaction with an online system(e-filing system) for filing individual income tax returns. The data was collected through questionnaire and then was tabulized and analyzed with the help of respective tests using SPSS, MS Excel and other required methods have been used. A survey has been used to collect primary data and questionnaire approach was used in final analysis. Single cross sectional descriptive research design was used to determine taxpayers’ perception. The result through questionnaires somehow discloses that most of the individuals facing problem regarding Lack of experience and knowledge in filing the return electronically and in the same questionnaires most of the individuals satisfy with the easiness and accuracy of e-filing. But when we go for overall experience of individuals regarding e-filing the still wants some improvement in the present e-filing system. Questionnaires have been filled by different level of employees both men and women of different age group, Income group and job profiles. This study is restrained to the taxpayers located in Lucknow city of Uttar Pradesh. So, the conclusion derived from the research cannot be made applicable as it is for the other parts of the states or other states.